Detection of soybean planted areas through orbital images based on culture spectral dynamics Detecção de áreas semeadas com soja por meio de imagens orbitais fundamentada na dinâmica espectral da cultura - Erivelto Mercante (Engenharia Agrícola, 2012)
The soybean is important to the economy of Brazil, so the estimation of the planted area and the production with higher antecedence and reliability becomes essential. Techniques related to Remote Sensing may help to obtain this information at lower cost and less subjectivity in relation to traditional surveys. The aim of this study is to estimate the planted area with soybean culture in the crop of 2008/2009 in cities in the west of the state of Paraná, in Brazil, based on the spectral dynamics of the culture and through the use of the specific system of analysis for images of Landsat 5/TM satellite. The obtained results were satisfactory, because the classification supervised by Maximum Verisimilitude - MaxVer along with the techniques of the specific system of analysis for satellite images has allowed an estimate of soybean planted area (soybean mask), obtaining values ​​of the metrics of Global Accuracy with an average of 79.05% and Kappa Index over 63.50% in all cities. The monitoring of a reference area was of great importance for determining the vegetative phase in which the culture is more different from the other targets, facilitating the choice of training samples (ROIs) and avoiding misclassifications. Dada a importância da soja para a economia do Brasil, a obtenção de estimativas da área semeada e da produção com maior antecedência e confiabilidade torna-se indispensável. Técnicas ligadas ao Sensoriamento Remoto podem ajudar na obtenção dessas informações com menores custos e subjetividade em relação aos levantamentos tradicionais. O trabalho tem por objetivo estimar a área semeada com a cultura da soja, durante safra de 2008/2009, em municípios do oeste do Estado do Paraná, com base na dinâmica espectral da cultura e por meio da utilização do sistema de análises específico para imagens do satélite Landsat 5/TM. Os resultados obtidos foram satisfatórios, pois a classificação supervisionada por Máxima Verossimilhança - MaxVer, juntamente com as técnicas do sistema de análises específico de imagens de satélites, permitiu uma estimativa de área plantada com a cultura da soja (máscara de soja), obtendo valores das métricas de Exatidão Global de 79,05% em média e Índice Kappa acima de 63,50%, em todos os municípios estudados. O acompanhamento de uma área-referência foi de grande importância para a determinação do estágio vegetativo em que a cultura mais se diferencia de outros alvos, facilitando a escolha das amostras de treinamento (ROIs) e evitando erros de classificação.